Menthol Mouth Rinsing Is More Than Just a Mouth Wash—Swilling of Menthol to Improve Physiological Performance - Erica H. Gavel; Kierstyn V. Hawke; David J. Bentley; Heather M. Logan-Sprenger; Heather M. Logan-Sprenger; Heather M. Logan-Sprenger (Frontiers in Nutrition, 2021)
Interventions that solely act on the central nervous system (CNS) are gaining considerable interest, particularly products consumed through the oral cavity. The oropharyngeal cavity contains a wide array of receptors that respond to sweet, bitter, and cold tastants, all of which have been shown to improve physiological performance. Of late, the ergogenic benefits of carbohydrate (CHO) and caffeine (CAF) mouth rinsings (MRs) have been widely studied; however, less is known about menthol (MEN). That the physiological state and environmental conditions impact the response each product has is increasingly recognized. While the effects of CHO and CAF MRs have been thoroughly studied in both hot and thermoneutral conditions, less is known about MEN as it has only been studied in hot environments. As such, this review summarizes the current knowledge regarding the MEN MR and exercise modality, frequency of the mouth rinse, and mouth rinse duration and compares two different types of study designs: time trials vs. time to exhaustion (TTE).